SOME METHODOLOGICAL APPROACHES TO STUDYING THE SOVIET EPOCH AT THE RUSSIAN HISTORY COURSES FOR HIGHER SCHOOL - Alexander B. Bezborodov (Moscow Polytechnic University, 2017)
The article considers the theoretical and methodological foundations for research practices applied while studying the Soviet period in the history ofRussia. The author reveals the methods of research of the Soviet reality and the channels of its influence on the modernity. He also defines the influence of the Soviet epoch symbols on the modern Russian daily occurrence. The author concludes that Russia will never go back to its Soviet past. But there has come into being a kind of stylistic model that presents such a return at the level of imitation.